Neurological Symptoms in Palliative Care Patients - Anneser, Johanna; Arenz, Victoria; Borasio, Gian Domenico (Frontiers in Neurology, 2018)
Background: Neurological expertise in palliative care may be required not only for patients with primary neurological disorders but also for patients with non-neurological diseases suffering from burdensome neurological symptoms. The aim of this study was to determine the prevalence of neurological diagnoses and symptoms in palliative care patients, as well as the related burden and impact on everyday life. Methods: We analyzed retrospectively the medical records of 255 consecutive patients from a tertiary medical center, at the time point of referral to an inpatient palliative care consultation service. In addition, 100 patients prospectively answered a questionnaire which included the assessment of neurological symptoms, as well as numeric rating scales (NRS) for quality of life, symptom specific burden and restrictions in everyday life. Results: Forty-one patients (16%) suffered from a primary neurological disease. Most decisions regarding the termination of life-sustaining measures concerned this group (20/22, 91%). Neurological symptoms (excluding pain) were documented in 122 patients (48%) with an underlying non-neurological disease. In the questionnaire study, 98/100 patients reported at least one neurological or neuropsychiatric symptom, most frequently sleeping problems (N=63), difficulty concentrating (N=55) and sensory symptoms (N=50). Vertigo/dizziness (N=19) had the greatest impact on everyday life (7.57/10 ± 2.17) and the highest symptom-specific burden (7.14 ± 2.51). Difficulty concentrating (restrictions in everyday life/ burden) and pain intensity were the only symptoms significantly correlated with quality of life (r = -0.36, p= 0.009/r= -0.32; p= 0.04; r= -0.327, p= 0.003). Conclusions: Neurological diseases and symptoms are frequent among palliative care patients and are often associated with a high symptom burden, which may severely affect the patients’ lives. It is thus of paramount importance to implement neurological expertise in palliative care.